L’annuncio del Concilio cinquanta anni fa. Una lettura nell’ambito della storia della Chiesa - von Teuffenbach, Alexandra (Alpha Omega, 2010)
Pope John XXIII, on January 25 1959, announced to the Cardinals gathered at St. Paul Outside the Walls - and at the same time to the entire world - that the Bishops of the Catholic Church would be called together in an Ecumenical Council. The reading /meaning that an historian gives to a past event is determined by his point of view. Even though the Church historians share the methodology and scientific rigor of secular (lay) historians, he should distinguish himself from the lay historian by the way in which he interpretats an event. Human movements within the Church and religious movements may only be correctly understood by one who fully understands the Church in her structure. In short, the meaning of ecclesial events can only be grasped within the faith.